Pengembangan Karakter dalam Upaya Meningkatkan Prestasi Siswa Sekolah Dasar Jambe Anom 1 Bondowoso - Wardhono, Adhitya; Qori’ah, Ciplis Gema; Puspito, Agung Nugroho; Ubaidillah, Mohammad; Kristianawati, Fany Indah; Febriani, Nawal Aprodita; Sinulingga, Trisna Handayani BR; Affiana, Alfina Nur; Wijayanti, Karmila Dwi; Salsabila, Ayu; Nasir, M Abd (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This study aims to evaluate and analyze the impact of the implementation of character development programs at SDN Jambe Anom 1. The focus of the study is to increase student motivation and achievement. Qualitative research is more investigative to produce data that cannot be obtained through statistical procedures. This character development program includes reinforcing positive values, ethics, and an attitude of responsibility. This research also carried out several activities to motivate students, such as sharing experiences and allowing students to express their dreams. In addition, this study also conducted several activities to improve student achievement. The results of this research are expected to encourage SDN Jambe Anom 1 students to achieve their goals